Impact of selected tramp elements in medium carbon steels on the deformation behavior of non-metallic inclusions and phase transformations - Julian Cejka; Isabell Gruber; Gerald Klösch; Susanne K. Michelic (Journal of Materials Research and Technology)
Scrap recycling is one of the major pillars of the steel industry's green transformation. It is important, however, to consider the available scrap's tramp element levels. While non-metallic inclusions (NMIs) and tramp elements are both considered to be part of steel cleanness, their interplay is hardly investigated. Therefore, this work focuses on the impact of tramp elements on NMIs in three medium carbon steels in solid state. The elements studied are copper, molybdenum, tin, and nickel. The deformation behavior of NMIs of the steels is evaluated by dilatometric deformation via the change of aspect ratio using automated SEM/EDS analyses. Furthermore, the effect of these tramp elements on the microstructure using quenching dilatometry is studied via dilatometric curves and light microscopy after etching. It is shown that especially copper (additions of 0.25 wt.-% and 0.5 wt.-%) impacts the deformation behavior of NMIs by reducing the change of aspect ratio and also increases the share of hard phases in the microstructure where in one steel bainite is formed while without copper the microstructure is ferritic-pearlitic with the same cooling rate. However, adding 0.1 or 0.2 wt.-% nickel causes the opposite effect on deformation and microstructure while the added levels of tin (0.03 wt.-%) and molybdenum (max. 0.08 wt.-%) have not influenced the NMI deformation behavior significantly. With the changes in NMI behavior and steel microstructure, fracture toughness has to be re-evaluated.